FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA - BUDIASIH, I G A N (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 1 (2009))
This research studies factors influencing the practices of income smoothing in manufacturing and financial firms listed on the Indonesian Stock Exchange during 2002-2006. Eckel Index is used to measure the income smoothing, while companies sizes are measured by total assets. Profitability is measured by ratio of before tax net profit to total assets, financial leverage is measured by debt to total assets ratio, and dividend pay out ratio by comparing dividend per share with earnings per share. Research population includes all manufacturing and financial firms listed on the Indonesian Stock Exchange from 2002 to 2006. Sample consists of 84 firms. Data are analyzed using multiple linear regressions with results that company size, profitability, and dividend pay out ratio have positive and significant impact on income smoothing practices. Financial leverage is the only factor that does not affect income smoothing practices.
Keywords: company size, profitability, financial leverage, dividend pay out ratio, income smoothing